Chronic Kidney Disease and Malignant Neoplasms: The Current State of the Problem - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; Zh. A. Murkamilova; I. O. Kudaibergenova; F. A. Yusupov (Архивъ внутренней медицины)
Chronic kidney disease is a risk factor for other organ disease. People with kidney disease have an increased risk of developing and dying from cardiovascular disease, and there is also evidence that the risk of cancer and cancer mortality may be increased in people with chronic kidney disease. Chronic kidney disease and malignant neoplasms are interconnected in both directions: cancer can cause damage to the kidney tissue directly or indirectly through the side effects of cancer treatment. In turn, chronic kidney disease, on the contrary, can be a risk factor for the development of malignant neoplasms. In addition, both pathological processes can share common risk factors. Chronic kidney disease can result from the use of chemotherapy drugs. Many of the existing and recently developed cancer chemotherapeutic agents are nephrotoxic and can contribute to renal dysfunction, which often manifests itself in terminal cancer. To date, therapeutic interventions to combat the progressive growth of cancer can accelerate the progression of chronic kidney disease. The article provides data on the interaction of chronic kidney disease and the development of malignant neoplasms. The nephrological aspects of the clinical picture of oncological diseases are considered. The mechanisms of the negative effect on the renal tissue of anticancer drugs — cisplatin, ifosfamide, methotrexate and cyclophosphamide — are discussed. Given the link between kidney disease and the development and treatment of cancer, the review article highlights the importance of interdisciplinary collaboration between oncologists and nephrologists to predict and prevent nephrotoxic effects of cancer chemotherapy, and as new treatments for malignant neoplasms are introduced, proper diagnosis and treatment of emerging malignancies is required. new renal toxic effects.